2015
DOI: 10.1021/acs.jpcc.5b07549
|View full text |Cite
|
Sign up to set email alerts
|

Role of Defects in Carbon Nanotube Walls in Deposition of CdS Nanoparticles from a Chemical Bath

Abstract: Multiwall carbon nanotubes (MWCNTs), as-prepared and annealed in an inert atmosphere, have been used as templates for growth of CdS nanoparticles from an aqueous ammonium solution of cadmium chloride and thiourea. Transmission electron microscopy and Raman spectroscopy revealed that formation of CdS nanocrystals on the raw MWCNT surface proceeds markedly faster than on the annealed one. Xray photoelectron spectroscopy showed a strong difference in the chemical state of the deposited CdS depending on the defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…The spectra were normalized to the intensity at 310 eV. The resonances at ~285.6 and ~291.7 eV correspond to electron transitions from 1s levels to π* and σ* states, respectively [ 56 , 57 ]. The peaks between ~287 and ~291 eV refer to the transitions involving carbon atoms bonded to functional groups and to defects [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The spectra were normalized to the intensity at 310 eV. The resonances at ~285.6 and ~291.7 eV correspond to electron transitions from 1s levels to π* and σ* states, respectively [ 56 , 57 ]. The peaks between ~287 and ~291 eV refer to the transitions involving carbon atoms bonded to functional groups and to defects [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…39,40 The presence of the S−S bonds on the surface of CdS nanoparticles grown on MWCNTs was previously explained by the S-rich surface of CdS and S−S−S linkages between surface atoms. 15 A high-energy component at 168 eV is attributed to sulfate species, which may develop at the MWCNT edges during their treatment by sulfuric acid. Moreover, sulfate species can arise due to the reaction of CdS nanoparticles with water.…”
Section: Resultsmentioning
confidence: 99%
“…14 Quantum-chemical calculations revealed that Cd 2+ ions and Cd(II) complexes should not interact with defect-free CNT walls, and nucleation and growth of CdS particles on the CNT surface more likely occur at edge states of graphene network. 15 It was reported that the presence of oxygen-containing groups on the CNT surface assists adsorption of Cd 2+ ions from an aqueous solution. 16 These functional groups along with defect sites appearing because of acid treatment or air oxidation of CNTs improve the nucleation of CdS on the nanotube surface.…”
Section: Introductionmentioning
confidence: 99%
“…Облучение ионами аргона создает радиационные дефекты, приводящие к разру-шению системы π-электронов sp 2 -углерода [25]. При этом, появление 2-x координированных атомов углерода в составе вакансионных дефектов, которые обладают высокой реакционной способностью [26], приводит к закреплению кислорода к стенкам N-МУНТ в виде различных функциональных групп. В результате это-го снижается количество свободных носителей заряда на поверхности углеродных нанотрубок.…”
Section: рис 4 рфэ-спектры валентной зоны исходных (1) и облучен-ныunclassified